2021
DOI: 10.1159/000516394
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Assembly by Ribosomal DNA: Emerging Roles in Disease Pathogenesis and Cancer Biology

Abstract: Unique repetitive elements of the eukaryotic genome can be problematic for cellular DNA replication and transcription and pose a source of genomic instability. Human ribosomal DNA (rDNA) exists as repeating units clustered together on several chromosomes. Understanding the molecular mechanisms whereby rDNA interferes with normal genome homeostasis is the subject of this review. We discuss the instability of rDNA as a driver of senescence and the important roles of helicases to suppress its deleterious effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 111 publications
0
17
0
Order By: Relevance
“…In our case, a, b, c = 3; N i = 1. Recent studies have shown that G4 structures not only destabilize the function of the genome, but may also contribute to the transcription regulation in rDNA and other regions of the genome [ 25 ]. Accordingly, it seems probable that G4 in the intact Q1 region should inhibit production of the pRNA transcript.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, a, b, c = 3; N i = 1. Recent studies have shown that G4 structures not only destabilize the function of the genome, but may also contribute to the transcription regulation in rDNA and other regions of the genome [ 25 ]. Accordingly, it seems probable that G4 in the intact Q1 region should inhibit production of the pRNA transcript.…”
Section: Discussionmentioning
confidence: 99%
“…An elegant review by Datta et al has nicely described the G-quadruplex biology in ribosomal DNA (rDNA). It has been demonstrated that G4 targeting in ribosomes and other loci play a vital role in regulation of biological processes and genomic stability and also provide a useful approach to combat with cancer ( Datta et al, 2021 ).…”
Section: G-quadruplex Structuresmentioning
confidence: 99%
“…31−33 While indiscriminate damage to nuclear DNA results in genotoxicity and unwanted side effects, targeting the nucleolus may trigger cancer cell death more selectively while sparing normal cells. 27,30 Many chemotherapeutics derived from anthraquinones, 34 fluorenones, 35 acridines, 36 and other polyaromatic chromophores show a high affinity for G-quadruplexes. Among these is quarfloxin, a fluoroquinoline derivative that accumulates in the nucleolus, 27 as demonstrated in lung adenocarcinoma cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another regulatory role of the G-quadruplex DNA may exist in the cell’s nucleolus, which is currently being pursued as a potential cellular target for anticancer therapeutics. The nucleolus plays a central role in the production of ribosomal RNA (rRNA) to sustain ribosome biogenesis during aberrant cell growth and proliferation. Ribosome biogenesis is tightly regulated by many cell signaling pathways that converge on the RNA polymerase I complex (Pol I) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation